2014
DOI: 10.1111/dme.12436
|View full text |Cite
|
Sign up to set email alerts
|

Decreased plasma chemerin levels in women with gestational diabetes mellitus

Abstract: Normal pregnancy is associated with increased circulating chemerin levels, which may act to reduce pregnancy-induced insulin resistance and prevent glucose intolerance. Women with gestational diabetes, however, have severely reduced chemerin levels that remain low after delivery, which may contribute to the insulin resistance, glucose intolerance and high type 2 diabetes risk associated with gestational diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 11 publications
3
21
1
Order By: Relevance
“…Garces et al (23) found no significant association of insulin and HOMA levels with chemerin, as did other independent studies (11,24,25). We found similar results for chemerin in pregnant women with GDM; however, other studies presented an association of chemerin with insulin resistance in pregnancy (26,27). Overall, it appears that chemerin may not be useful in predicting GDM.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Garces et al (23) found no significant association of insulin and HOMA levels with chemerin, as did other independent studies (11,24,25). We found similar results for chemerin in pregnant women with GDM; however, other studies presented an association of chemerin with insulin resistance in pregnancy (26,27). Overall, it appears that chemerin may not be useful in predicting GDM.…”
Section: Discussionsupporting
confidence: 78%
“…Many studies demonstrated increased RBP-4 concentrations in GDM (14,29), while others did not show a relationship of chemerin with GDM or normal glucose tolerance, as in our study (30,31). One study even reported that RBP-4 concentration was decreased in GDM (26). A study was conducted by Wójcik et al (13) concerning the relationship between adipose tissue hormones and GDM.…”
Section: Discussioncontrasting
confidence: 46%
“…Contrary results are reported by Hare et al, as low Chemerin levels were observed in GDM pregnant females (n=nine) compared to normal pregnant women (n=eight). They suggest that the low Chemerin levels during GDM pregnancy may lead to insulin resistance and a higher level in normal pregnancy may have a protective effect to reduce pregnancy induced insulin resistance [19].…”
Section: Discussionmentioning
confidence: 99%
“…Participants and characteristics have previously been reported (Bonde et al, 2013;Hare et al, 2014).…”
Section: Subjects Methods and Registration Of Protocolmentioning
confidence: 99%